2018
DOI: 10.1186/s12882-018-0955-9
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy in experimental chronic kidney disease is associated with reduced expression of cardiac Kruppel-like factor 15

Abstract: BackgroundLeft ventricular hypertrophy (LVH) increases the risk of death in chronic kidney disease (CKD). The transcription factor Kruppel-like factor 15 (KLF15) is expressed in the heart and regulates cardiac remodelling through inhibition of hypertrophy and fibrosis. It is unknown if KLF15 expression is changed in CKD induced LVH, or whether expression is modulated by blood pressure reduction using angiotensin converting enzyme (ACE) inhibition.MethodsCKD was induced in Sprague–Dawley rats by subtotal nephre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Our results suggest that sex-specific changes in CKDrelated cardiac structural remodeling are present in this mouse model. Considering that LV hypertrophy is a common morphology that can predict the risk of adverse cardiovascular events in CKD patients, and that sex differences exist in the manifestation and progression of CKD in humans, with female sex being a protective factor in CKD-associated CVD risk, we conclude that an advantage of this model is its ability to study these CKD-induced CVD sex differences 31,32 .…”
Section: Discussionmentioning
confidence: 98%
“…Our results suggest that sex-specific changes in CKDrelated cardiac structural remodeling are present in this mouse model. Considering that LV hypertrophy is a common morphology that can predict the risk of adverse cardiovascular events in CKD patients, and that sex differences exist in the manifestation and progression of CKD in humans, with female sex being a protective factor in CKD-associated CVD risk, we conclude that an advantage of this model is its ability to study these CKD-induced CVD sex differences 31,32 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that KLF15 is an important negative regulator of cardiac hypertrophy, and loss or repression of KLF15 leads to left ventricle hypertrophy, due to lack of inhibition of pro-hypertrophic transcription factors and stimulation of trophic and fibrotic signaling pathways [ 50 ]. Importantly, single nucleotide polymorphisms in KLF15 have been associated with cardiac hypertrophy in patients with diabetes mellitus [ 51 ], and in experimental chronic kidney disease, ventricular hypertrophy is associated with reduced expression of cardiac KLF15 [ 52 ]. In the present study, two AF patients in this family developed left ventricle hypertrophy, highlighting the need for regular echocardiographic evaluation of cardiac structure and function for the mutation carriers to make an early diagnosis of left ventricle hypertrophy, a common harbinger of heart failure and sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In patients with hypertension, the period of high pressure reaches 160-190mmhg and low pressure reaches 100-109 is clinically characterized by LVH and organic diseases in the heart, brain and kidney system. 10 , 11 The heart and blood vessels are the main target organs for the pathophysiological effects of hypertension. Hypertensive heart disease, characterized by symmetrical hypertrophy, asymmetric hypertrophy and extendible hypertrophy, is known as hypertensive heart disease due to cardiac hypertrophy and expansion caused by long-term high pressure load, cardiomyocyte hypertrophy and interstitial fibrosis changes.…”
Section: Discussionmentioning
confidence: 99%